2005
DOI: 10.1128/jcm.43.9.4807-4810.2005
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Total Plasma Load of Torquetenovirus (TTV) and TTV Genogroups Carried

Abstract: In 239 torquetenovirus-positive people, multiple-genogroup infections were common and associated with higher viral loads than would be expected from simple additive effects. The latter observation was restricted to the infections which included both genogroups 1 and 3, pointing to the possible existence of some kind of infection facilitation between these genogroups.Torquetenovirus (TTV), formerly known as TT virus, was discovered in 1997 by Japanese workers in the blood of a patient with cryptogenetic hepatit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
60
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 17 publications
6
60
4
Order By: Relevance
“…TTV is common in blood donors [68] and a high percentage of the general population exhibits chronic viraemia (around 80% in some areas) [69]. In the control group the minor alleles frequencies of IL6 G-174C (-174 C: 0.2133) [70], ACE ID (I: 0.4767) [71] and ATR1 A1166C (1166 C: 0.2967) [62,72] were in the range of data reported for other worldwide populations.…”
Section: Discussionmentioning
confidence: 56%
“…TTV is common in blood donors [68] and a high percentage of the general population exhibits chronic viraemia (around 80% in some areas) [69]. In the control group the minor alleles frequencies of IL6 G-174C (-174 C: 0.2133) [70], ACE ID (I: 0.4767) [71] and ATR1 A1166C (1166 C: 0.2967) [62,72] were in the range of data reported for other worldwide populations.…”
Section: Discussionmentioning
confidence: 56%
“…All samples from each patient were assayed in a single run and in triplicate, and at least two independent DNA extractions for each sample were examined. The DNA extracts obtained at time zero were also typed with a previously described panel of five distinct PCR assays (12), each specific for one of the genogroups into which TTVs are subdivided. At the start of the study, the patients had viral loads ranging from 4.7 to 6.8 log copies per ml of plasma and harbored between 1 and 3 TTV genogroups (Table 1).…”
mentioning
confidence: 99%
“…We observed the highest seroprevalence rates with TTV6 LTT6 (Gr2) in children and TTV13 3h (Gr3a) in adults, this difference being either coincidental or genuinely age-specific. In comparison, PCR studies among adults have revealed TTV Gr1 and Gr3 to be the most prevalent genogroups, and Gr2 to be rare (Biagini et al, 2006;Maggi et al, 2005). The DNA prevalences of Gr1-5 were 70, 2, 73, 48 and 21 % in a French study, and 34, 2, 24, 2 and 12 % in an Italian study (Biagini et al, 2006;Maggi et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Seroconversions occurred, except for TTV3 HEL32, at overall rates of 5-7 % of the initial seronegative sera, whilst a number of children that were initially seropositive for a single strain later acquired multiple-genogroup antibodies. This indicates that the simultaneous presence of several TTV genogroups in the human body (de Villiers et al, 2002;Jelcic et al, 2004;Maggi et al, 2005;Niel et al, 2000;Okamoto et al, 2001) can be due to sequential infections, and that antibodies against certain TTV types are non-protective against others. Interestingly, seroreversions were seen among all TTV strains, at rates of 10-75 % of the initial seropositive children, explaining the lower seroprevalences among children aged 4-7 years.…”
Section: Discussionmentioning
confidence: 99%